Influence of the Finite Size Effect on Properties of a Weakly Interacting Bose G as in Improved Hatree-fock Approximation - Nguyen, Van Thu (H. : ĐHQGHN, 2018)
The finite size effect causes many interesting behaviors in properties of a weakly interacting Bose gas. These behaviors were considered in one-loop approximation of quantum field theory. In this paper the influence is investigated in improved Hatree-Fock approximation, which gives more accurate results.